Religion-State Relations: Roland Barthes' Semiotic Analysis of the Architecture of the Putra Putrajaya Mosque, Malaysia - Angger Sasono Jati; Moch. Mukhlison (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
The Putra Putrajaya Mosque is a symbolic representation of Malaysia's religious-state relations that constitutionally establishes Islam as the Religion of the Federation. However, an analysis of 121 traveller reviews on Instagram and TripAdvisor showed that 90.9% of visitor narratives only highlighted visual aesthetics without touching the ideological dimension of architecture, indicating the workings of mythical mechanisms that naturalize messages of power. This research aims to uncover the denotative, connotative, and mythical meaning of the architectural elements of the Putra Mosque as a representation of religious-state relations, as well as dismantle the mechanism of exnomination that makes the ideological construction of the state appear to be aesthetically justified. The study used a qualitative approach with the Roland Barthes semiotics framework through triangulation of field observations, in-depth interviews with five multi-layered interviews, and netnography of 121 tourist reviews. The results of the study showed that the seven architectural elements of the spatial position facing the Prime Minister's Office, the capacity of 15,000 worshippers, the pink granite dome, the 116-meter octagonal tower, the integration of Lake Putrajaya, arabesque ornamentation across civilizations, and the dual functions of tourism and worship work as a layered marking system. Connotatively, these elements build the Islamic narrative as the moral foundation of an institutionalized modern state. At the mythical level, exnominations have proven to be effective in disguising the ideological content behind visual beauty so that it is accepted by the public as natural naturalness.